Adaptive Event Management Capability: The Framework for Event Organizers’ Operational Resilience in a Dynamic Tourism Environment - Anawangwulan, Grace Jeanie (Jurnal Indonesia Sosial Sains, 2026)
The event organizer industry is part of the tourism service sector, which has project-based operational characteristics with a high degree of variability. Unlike the recurring service sector, events take place within a limited time frame, involve many parties, and are influenced by unpredictable environmental conditions. These conditions mean that a static, planning-based operational management approach cannot always guarantee the stability of event implementation. This study aims to develop a conceptual framework of Adaptive Event Management Capability as a model of operational resilience for event organizer organizations. The study uses a conceptual approach through the integration of dynamic capability theory, organizational resilience, and service management. The analysis was conducted through a literature synthesis to construct a theoretical framework of adaptive capabilities in project-based service organizations. The results of the study indicate that the operational resilience of event organizations is shaped by four key capabilities, namely anticipatory capability, responsive capability, transformative capability, and sustainable stabilization capability. These four capabilities form an operational learning cycle that determines the consistency of organizational performance. These findings confirm that the success of activities is determined not only by the quality of planning but also by the organization’s ability to interpret and adjust its actions to changing situations. This research contributes to the development of tourism service management studies by positioning the stability of operational processes as a key factor in the performance of project-based organizations.